Korelasi Komunikasi Interpersonal Antara Ibu dan Anak terhadap Kemampuan Berbicara Anak Usia 4-5 tahun di RA Miftahul Huda: Correlation of Interpersonal Communication Between Mother and Children to Speaking Ability for 4-5 Years Old Children in RA Miftahul Huda Ciwaringin-Cirebon - Fauziah, Sifa; Nuryanto, Tato; Kamiludin, Udin (Balai Bahasa Provinsi Papua, 2022)
Based on the observation of the speaking ability of children aged 4-5 years in RA. Miftahul Huda is not sufficient. This study aims to describe interpersonal communication, speaking skills of children aged 4-5 years and the correlation between mother and child interpersonal communication on speaking skills of children aged 4-5 years. The research method used is a quantitative correlational study. Based on the results of the analysis of interpersonal communication categories of high (0%), moderate (100%), and low (0%). The speaking ability of children aged 4-5 years is categorized as high (0%), moderate (100%), and low (0%). There is a significant correlation between mother's interpersonal communication on the speaking ability of children aged 4-5 years, because tcount is greater than ttable worth 0.673>2.021.